ANALISIS LAPORAN REALISASI ANGGARAN UNTUK MENILAI KINERJA KEUANGAN PADA KANTOR BADAN PENDAPATAN DAERAH KABUPATEN OKU - Dona, Eka meiliya; Lestari, Verza Ayu (Balance : Jurnal Akuntansi dan Bisnis, 2020)
The purpose of the study was to determine the financial performance of the OKU Regency Revenue Agency office analyzed from the 2013-2017 budget realization report. The method used is descriptive quantitative using economic levels, efficiency, and effectiveness. From the results of the analysis it was concluded that the financial performance based on the analysis of economic levels in 2013-2017, namely varied economic rates averaged 89.48% with criteria quite economical, this shows the ability of the government to economize spending is quite good. The level of efficiency in the OKU Regency Revenue Agency increased from year to year, the average efficiency level in 2013-2017 was 62.58% with efficient criteria because the realization of local tax revenue was greater than the costs incurred to collect local taxes, this shows the government's ability to streamline income and expenditure is good. And the level of effectiveness of PAD revenue is fixed or stable from year to year, the average level of effectiveness in 2013-2017 is 114.39% with very effective criteria, this shows the ability of the government to achieve the revenue budget set by the OKU Regency Revenue Agency isvery effective.